Feeling nature in writing: environmental education in the EFL writing course - Lestari Setyowati; Sari Karmina; Ahmad Heki Sujiatmoko; Nova Ariani (Journal on English as a Foreign Language, 2022)
Environmental degradation increases the threat to ecological disaster. Thus, environmental education is crucial for disaster mitigation. This study is intended to investigate the students